Characterization of a fast gas analyzer based on Raman scattering for the analysis of synthesis gas - Eichmann, Simone; Weschta, Martin; Kiefer, Johannes; Seeger, Thomas; Leipertz, Alfred (Review of Scientific Instruments, 2010)
A sensor system for fast analysis of synthesis gas (mixtures of CO and H2) is proposed and characterized. The system is based on spontaneous Raman scattering, which enables simultaneous concentration measurements of all relevant species. For typical synthesis gas applications, this system has to face large variations of temperature and pressure. In addition, strong fluctuations in mixture composition may occur, which lead to rather inconvenient signal intensities. In this paper, we describe a low resolution spectrometer designed to function as a synthesis gas sensor and characterize pressure and temperature effects on concentration measurements. In addition, the use of different spectral ranges and calibration strategies is investigated in view of measurement accuracy and precision. © 2010 American Institute of Physics.
UnivIS-Import:2015-03-09:Pub.2010.tech.FT.FT-KLMEFK.charac